Using Sentiment Analysis of Online Hotel Reviews To Explore the Effect of Information and Communication Technologies on Hotel Guest Satisfaction - Salma Cherdouh; Abdenacer Kherri; Ayoub Abbaci; Salim Kebir (Journal of Tourismology)
Online hotel reviews are a rich source of information regarding drivers of customer satisfaction or dissatisfaction with hotel services. In this paper, we study the impact of information and communication technologies (ICT) on the satisfaction of customers of 144 Algerian hotels through the analysis of 11310 online user reviews. The methodology adopted is based on the analysis of the sentiments expressed in the user reviews from one of the most used travel platforms, TripAdvisor. The results indicate that sentiment towards ICT contributes to satisfaction but not as much as sentiment towards other non-ICT services. Furthermore, we identified individually which ICTs contribute to satisfaction. We found that ICTs related to booking, comfort and entertainment were the ones that significantly contributed to satisfaction, while ICT related to safety and security did not. We believe that this study contributes to the literature because it uses innovative natural language processing techniques as opposed to traditional questionnaire-based approaches. Moreover, this study was conducted in a developing country where ICT adoption differs from that of developed countries.